Integration of Pedagogical Knowledge in the Light of Questions about the Empirical Foundations of General Pedagogy and Understanding of the Concept of Generality - Waga, Leszek (Paedagogia Christiana, 2018)
The main purpose of the article is to show that the studies undertaken by pedagogues, regarding both the experimental foundations of pedagogy and generality, have some common points and that an in-depth reflection on those issues highlights the postulate to treat pedagogical knowledge in an integral manner. The first part presents the relationship between the issue of the empirical foundations of pedagogy and the problems of integrity of pedagogical knowledge; the second part – the relationship between the concept of generality and the problems of integrity, and the concluding part presents a proposed understanding of general pedagogy as integral pedagogy in which the approach towards both empirical sources of pedagogical knowledge and the generality category are the integrating element. The analyses carried out made it possible to consider general pedagogy as a specific type of reflection on education, or as a mental structure, the tasks of which include integration of the entire pedagogical knowledge. Fulfilment of that task may valourise general pedagogues' scientific activity as recognition of the fact that in the experienced research reality there are incomprehensible elements that demand generality (celebration) build the pedagogue's authority.